Limited role of HLA DQ2/8 genotyping in diagnosing coeliac disease. Issue 1 (February 2017) - Paul, Siba P; Hoghton, Matthew; Sandhu, Bhupinder
The European guidelines for diagnosing coeliac disease in children were revised in 2012. These recommend that in symptomatic children, a diagnosis of coeliac disease can be made without small-bowel biopsies provided their anti-tissue transglutaminase (anti-tTG) titre is >10 times of upper-limit-of-normal (>10×ULN) and anti-endomysial antibody is positive. In order to firm up the diagnosis in these children with very high anti-tTG titre, HLA-DQ2/DQ8 should be checked and be positive. Approximately 25–40% of white Caucasian population has HLA-DQ2/DQ8 haplotype. However, only 0.1–1% of the population will develop coeliac disease. Therefore, HLA-DQ2/DQ8 testing must not be done to 'screen' or 'diagnose' children with coeliac disease. Its use by paediatricians should be limited to children with anti-tTG>10×ULN, where the diagnosis of coeliac disease is being made on serology alone. A review of case referrals made to a tertiary paediatric gastroenterology centre in Southwest England demonstrated that HLA-DQ2/DQ8 testing is being requested inappropriately both in primary and secondary care suggesting a poor understanding of its role in diagnosis of coeliac disease. This article aims to clarify the role of HLA-DQ2/DQ8 testing for clinicians working in non-specialist settings.